The Absent and Silenced Voice in Newspaper Representations of Filipina Victims of Homicide in Australia - Saroca, Nicki (Review of Women's Studies, 2023)
This article explores the absent and silenced voice in Australian newspapers through case studies of two Filipino women - Nenita Westhof and Marylou Orton, who were victims of homicide in Australia. It draws on a feminist discourse analysis of newspaper articles and interviews conducted with their families and friends. While raising particular conceptual, methodological and ethical concerns, the method used is one way we can hear the stories of those who do not have a voice in the present. Analysing newspaper representations in light of the interviews provides an entirely different, more accurate and just reconstruction of the women's lives. Media representations of Nenita and Marylou bore little resemblance to their 'lived reality'. In most instances, journalists did not acknowledge that the women were victims of domestic violence. Further, sexist, racist and class-based discourses constructed Nenita and Marylou in accordance with dominant representations of Filipino women in Australia. They were held accountable for their deaths, while their abusive male partners were frequently portrayed as victims of women who abused them. The article argues such representations sensationalise the issues, misrepresent violence as the women's fault and shift the responsibility from the perpetrator onto the victim. In the process, they silence women's voices.